The Relationship between Private Equity and Economic Growth - Gudiškis, Karolis; Urbšienė, Laimutė (Ekonomika, 2015)
The purpose of this paper is to provide empirical evidence on the relationship between private equity, innovations, and economic growth in 13 European countries by using quantitative analysis. The objectives of the paper are as follows: description of private equity; examination of the relationship between private equity and economic growth; investigation of the methods used in the related topics; description and testing of the data used in the empirical research; estimation of the empirical model; reporting and interpretation of the results. The systematic, comparative and critical analysis of the scientific literature is used for determining the relationship between private equity, innovation, and economic growth. Further, the data are tested using unit root tests. The panel vector autoregressive model, Granger causality, impulse response, and variance decomposition analyses are applied for short-term causality. The main findings are as follows: granted patents are the most important measure of innovation, which influence private equity and economic growth. However, patents should be considered an input rather than an output of the private equity investment process. Therefore, granted patents attract private equity, and private equity impacts economic growth by commercializing granted patents in the short term.
Keywords: private equity investments; economic growth; panel VAR; the Granger causality